A Word & Character N-Gram based Arabic OCR Error Simulation model - Ezzat, Mostafa; ElGhazaly, Tarek Ahmed; Gheith, Mervat (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper provides a new model aimed to enhanceArabic OCR degraded text retrieval effectiveness. The proposed model based onsimulating the Arabic OCR recognition mistakesbased on both, word based and Character N-Gram approaches. Then we expand the user search query using the expected OCR errors. The resulting search query expanded gives high precision and recall values in searching Arabic OCR-Degraded text rather than the original query. The proposed model showed a significant increase in the degraded text retrieval effectiveness over the previous models. The retrieval effectiveness of the newmodel is %93, while the best effectiveness published for word based approach was %84 and the best effectiveness for character based approach was %56.